A better ballot box?. - Mercuri, R. (IEEE spectrum)
Election officials are examining technologies to address a wide range of voting issues. The problems observed in the November 2000 US election accelerated existing trends to get rid of lever machines, punch-cards, and hand-counted paper ballots and replace them with mark-sense balloting, Internet, and automatic teller machine (ATM) kiosk style computer-based systems. An estimated US 2-4 billion dollars will be spent in the United States and Canada to update voting systems during the next decade. Voting online might enable citizens to vote even if they are unable to get to the polls. Yet making these methods work right turns out to be considerably more difficult than originally thought. New electronic voting systems pose risks as well as solutions. As it turns out, many of the voting products currently for sale provide less accountability, poorer reliability, and greater opportunity for widespread fraud than those already in use. This paper discusses the technology available and how to ensure accurate ballots.